The Impact of Applying Relaxation Techniques in Reducing Stress in Menstruating Adolescents in the Coastal and Island Areas - Irma Ika Sari; Arindiah Puspo Windari (Indonesian Journal of Global Health Research, 2024)
Menstruation is the periodic and cyclic discharge of blood, mucus, and cell debris from the uterine mucosa, accompanied by the shedding (desquamation) of the endometrium, which starts about 14 days after ovulation. The objective of this study is to examine the effect of applying relaxation techniques in reducing stress among menstruating adolescents at SMA Negeri 1 Waisala, Seram Bagian Barat District in 2023. The research design used is an experimental design with a one-group pretest-posttest approach. The research was conducted at SMA Negeri 1 Waisala in August 2023. The sampling technique used in this study follows Slovin's formula, which represents 30% of the total students, or 30% of 167 students, resulting in a sample of 56 participants. The research instrument used is a questionnaire. There are 56 students who are menstruating at SMA Negeri 1 Waisala. The data analysis was conducted using a dependent t-test (t-paired) if the data followed a normal distribution. The results show a significant effect of applying relaxation techniques in reducing stress among menstruating adolescents at SMA Negeri 1 Waisala, with a p-value of 0.000.